Assessment of Implementation of Six Sigma DMAIC approach in a Casting unit - Goraya, Dr. Harjit Singh; Gandhi, Dr. Surjit Kumar (Journal of Advanced Research in Information Technology, Systems and Management, 2024)
Six-Sigma approach is a management approach of achieving major enhancements in a process through systematic elimination of waste. In this case, the casting unit under study was experiencing a rejection rate of 30%. The main aim of the study is to identify various causes of occurrence of blowholes and identify corresponding remedies for these defects by systematic implementation of DMAIC cycle. Preventive and corrective actions were recommended to reduce the blow holes defect and overall improvement is validated through two-proportion test. Results of investigation demonstrated the net significant reduction of blowhole defect from 28,111 to 9708 PPM (parts per million)  which results in the net savings of rupees 12,56,640 anually.